Variation in Current Guidelines for Fluoride Varnish Application for Young Children in Medical Settings in the United States - Sarah L. Goff; Grace Gahlon; Kimberley H. Geissler; Andrew W. Dick; Ashley M. Kranz (Frontiers Media S.A., 2022)
BackgroundThe United States Preventive Services Task Force recommends that medical providers apply fluoride varnish (FV) to the teeth of all children under 6 years of age, but fewer than 10% of eligible children receive FV as recommended. Prior studies suggest that variation in clinical guidelines is associated with low uptake of other evidence-based health-related interventions, but consistency of national guidelines for the delivery of FV in medical settings is unknown.MethodsEligible guidelines for application of FV in medical settings for children under 6 years of age were published in the past 10 years by national pediatric or dental professional organizations or by national public health entities. Guidelines were identified using the search terms fluoride varnish + [application; guidelines, or recommendations; children or pediatric; American Academy of Pediatrics (AAP); American Academy of Pediatric Dentistry] and a search of Guideline Central. Details of the guidelines were extracted and compared.ResultsTen guidelines met inclusion criteria. Guidelines differed in terms of periodicity recommendations and whether FV was indicated for children with a dental home or level of risk of dental caries.ConclusionNumerous recommendations about FV delivery in medical settings are available to pediatric medical providers. Further study is warranted to determine whether the variation across current guidelines detected in this study may contribute to low FV application rates in medical settings.